A call to incorporate a reproductive justice agenda into reproductive health clinical practice and policy - Gilliam, Melissa L.; Neustadt, Amy; Gordon, Rivka (Contraception, 2009)
Keywords: approches et analyses; contraception; discipline; droits des femmes*; intersectionnalité; inégalités; justice reproductive; justice sociale; médecine; ressource en ligne; santé; santé des femmes*; sciences; sciences humaines; sexologie; systèmes d'oppressions; thématiques

The Role of Gender and Ethnicity in Perceptions of Rape and Its Aftereffects - Schneider, Lawrence J.; Mori, Lisa T.; Lambert, Paul L.; Wong, Anna O. (Sex Roles : A Journal of Research, 2009)
Caucasian-, Hispanic-, and Asian-American male and female students (n = 764) attending a California (USA) public university reported their perceptions of sexual assault. After reading a rape vignette, participants gave their impressions of the victim; estimated time needed for recovery and treatment; and recommended a sentence for the assailant. Half of the sample received information regarding state sentencing guidelines. Relative to female participants, males perceived the victim as more responsible. Caucasian-American males had stronger reservation about the victim’s judgment. Males were less inclined to assign blame than were females. Ethnicity was the only factor influencing perceptions of recovery. Ethnicity and sentencing guidelines, but not gender, impacted imprisonment decisions. Issues impeding a unified theoretical understanding of perceptions of rape victims were considered.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; californie; cours; discipline; intersectionnalité; perception; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; thématiques; viol; violences; états-unis